Diffuse large b-cell lymphoma of the ocular adnexa with flow cytometry analysis and review of the literature. Issue 2 (March 2023) - Mitamura, Mizuho; Kase, Satoru; Suzuki, Yasuo; Sakaguchi, Takatoshi; Suimon, Yuka; Sinohara, Toshiya; Shimizu, AI; Matsuno, Yoshihiro; Sakai, Hajime; Kase, Manabu; Ishida, Susumu
Purpose: The aim of this study was to evaluate the clinicopathological features and flow cytometry (FCM) of tumor tissues in ocular adnexal diffuse large B-cell lymphoma (DLBCL). Methods: This retrospective, multicenter case study was designed to evaluate the clinical and immunohistochemical features of tumors. DLBCL was diagnosed based on histopathology, immunoglobulin (Ig) heavy chain gene rearrangement, and FCM in all surgically removed periocular tumor tissues. This study involved assessing percentages (%) of B-cell/T-cell markers, a natural killer cell marker, and cell-surface Ig kappa/lambda (κ/λ) expression measured by FCM analysis in tumor tissues. Results: Eleven DLBCL patients (4 men and 7 women) with 11 tumors were enrolled in this study. The median age at the time of initial presentation was 73 years. The tumor cells were immunohistochemically positive for cluster of differentiation (CD) 20, while CD5 was negative in all 8 cases tested. At the time of ophthalmic diagnosis, two cases already showed systemic dissemination of DLBCL throughout the body. FCM of tumor tissues detected a high percentage of B-cell markers including CD19 and CD20 in all 11 tumors. One case with high CD10 levels in FCM was histologic transformation from follicular lymphoma. One case with a relatively low CD20 population involved a history of systemic treatments including intravenous rituximab. Conclusion: Although caution should be exercised when interpreting the data, FCM is useful for not only supportive diagnosis complementary to immunohistochemistry, but also facilitates a better understanding of immunopathology including histologic transformation of follicular lymphoma to DLBCL in the ocular adnexa.